“Cultura organizacional y su efecto en el resultado empresarial en las microempresas comerciales del cantón La Maná, provincia de Cotopaxi. Año 2020. - Cela Jacho, Byron Adrian (2021)
The study of organizational culture and its effect on business results was developed in the microenterprises of the commercial sector of the canton of La Maná in order to identify the elements of the organizational culture of 150 commercial microenterprises, which direct these efforts to improve the results in the administrative management and in the economic and financial area of this important sector of the economy of La Maná. In order to obtain the necessary data in the research, the deductive method was used, which facilitated the identification of the intangible elements of the organizational culture in the micro enterprises under study and, with the use of the analytical method, through its practical application, it was possible to classify, tabulate, record, compare and analyze the information obtained in the surveys applied to a total of 378 employees and 378 clients of the micro enterprises in the sample under study. The information obtained shows that 30% of the employees state that they strongly agree with the application of intangible elements, 52.5% of the cases state that they agree with this aspect. In reference to the quality of the service provided by the members of the microenterprises, 26.4 % of those consulted stated that they strongly agreed, 37.6 % indicated that they agreed with the quality of the service. Similarly, in relation to customer satisfaction, 29.5 % of the cases state that they strongly agree, 30.8 % of the customers say that they agree with this. At the beginning of the business activities the owners hired 213 employees and currently there are 466 employees, which represents a growth of 120 percent. The accounting and financial study shows that the average assets amount to $70,083.3, while liabilities reflect a value of $26,366.7. The total annual sales volume averages $106,583.3, while the cost of sales represents $51,216.7, resulting in an operating profit of $55,366.7. It is estimated that the sector under analysis presents a liquidity index of 2.66; maintaining a debt index of 38%, with an operating profit margin of 52% and a return on equity of 127%, which leads to the conclusion that the intangible elements of the organizational culture within the commercial microenterprises have a positive impact on the commercial environment.